Becoming Canadian: Folk Literary Innovation in the Memoirs of Yiddish-Speaking Immigrants to Canada - Lightstone, Vardit (Canadian Jewish Studies / Études juives canadiennes, 2021)
This article considers the ways Yiddish-speaking immigrants to Canada creatively adapted folklore that they learned in “the old home” in order to make it fit their new Canadian contexts, and in doing so created new hybrid folklore and identities. To do this, I discuss the autobiographical texts of three people who migrated between 1900 and 1930, J.J. Goodman’s Gezamelte Shriften (Collected Writings) (Winnipeg: 1919), Michael Usiskin’s Oksn un Motorn (Oxen and Tractors) (Toronto: 1945), and Falek Zolf ’s Oyf Fremder Erd (On Foreign Soil) (Winnipeg: 1945). I argue that these personal narratives offer important insights into how the first major wave of Eastern European Jewish immigrants to Canada formed and expressed Canadian-Eastern European Jewish culture.